Vapor chamber and preparation method and application thereof
By adopting the micro-nano multi-stage pore structure of the liquid absorbing core and support column design in the heat-smooth plate, the problem of heat dissipation limit of the traditional heat-smooth plate is solved, and efficient heat dissipation performance and reliability are achieved. It is suitable for electronics with high heat flow density equipment.
Patent Information
- Application Number
- CN202411316219.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-20
AI Technical Summary
The pure copper mesh liquid-absorbing core of the traditional heat-smoothing plate cannot control the pore structure, resulting in the heat dissipation limit, which cannot meet the heat dissipation needs of high heat flow density such as 5G base stations, and the amorphous microstructure of the porous medium increases the difficulty of fluid transmission prediction and structural adjustment. .
The liquid absorbent core with a micro-nano multi-stage pore structure is used to prepare a conformal porous metal foam structure by electrodeposition method of PS microspheres and binder, and combine the support column and vacuum cavity design to improve heat transfer efficiency and reliability.
It achieves high heat transfer capability and efficiency, meets the heat dissipation needs of large-area heat-smoothing plates, and can be used in heat pipes and other radiators with high capillary driving force, reducing production costs and complexity.
Smart Images

Figure BDA0005052294850000071 
Figure BDA0005052294850000081 
Figure HDA0005052294860000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of vapor chambers, and in particular to a vapor chamber and a preparation method and application thereof. Background Art
[0002] The booming development of electronic information technology, especially communication and detection technology, has greatly promoted the widespread application of electronic products and industrial instruments, such as mobile phones and base stations, profoundly changing people's lifestyles and improving their quality of life. Vapor chambers are widely used in electronic equipment heat dissipation, and the liquid wick is the core part of the vapor chamber.
[0003] The pure copper mesh wick used in traditional heat spreaders cannot control the pore structure and has a heat dissipation limit. It can only be used for low-end heat dissipation and can no longer meet the requirements of 5G base station heat dissipation. Currently, porous media are generally used as capillary materials, but the microstructure of porous media is amorphous, the pore positions are irregularly distributed, and there are no clearly defined pore units. Since these porous media do not have highly ordered microscale features, it is more difficult to accurately predict fluid transmission and precisely adjust structural features, and the highly tortuous network between pores makes them show huge hydraulic resistance.
[0004] In view of this, this application is filed. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a heat spreader and its preparation method and application. The heat spreader contains a liquid-absorbing core with a micro-nano multi-level pore structure, has a large heat transfer capacity, high heat transfer efficiency, and high reliability, and can be used to make a large-area heat spreader.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A heat spreader comprises a bottom plate, a top plate, a liquid wick with a micro-nano multi-level pore structure and a support column, wherein the bottom plate and the top plate form a vacuum cavity, the liquid wick with the micro-nano multi-level pore structure and the support column are located inside the vacuum cavity, the support column connects the bottom plate and the top plate, and the vacuum cavity is filled with working liquid.
[0008] The liquid-absorbing core with a micro-nano multi-level pore structure of the present invention has a micron structure and a conformal porous metal foam structure with nanopore characteristics, and has the characteristics of large capillary driving force, high permeability and small flow resistance. This kind of heat spreader has low production cost, simple method, large heat transfer capacity, high heat transfer efficiency and high reliability, and can be used to make a large-area heat spreader to meet the heat dissipation requirements of electronic equipment with high heat flux density; and the micro-nano multi-level structure of the present invention can be further used for the inner wall of a heat pipe that requires a high capillary driving force and other radiators to meet the needs of rapid heat dissipation, and has broad application prospects.
[0009] As a preferred embodiment of the present invention, the thickness of the bottom plate and the top plate are both 0.01-0.1 mm, and the materials of the bottom plate and the top plate are both copper alloy, aluminum alloy, stainless steel or titanium alloy.
[0010] The present invention also provides a method for preparing a vapor chamber, comprising the following steps:
[0011] (1) providing a bottom plate, wherein the surface of the bottom plate has a wire mesh or a groove;
[0012] (2) mixing the PS microspheres and the binder uniformly to obtain an emulsion, applying the emulsion to the surface of the base plate, drying, depositing an electrodeposition liquid on the surface of the base plate by an electrodeposition method, soaking in an organic solvent, and annealing to obtain a liquid wick having a micro-nano multi-level pore structure;
[0013] (3) placing the support column and the base plate on the stamping die and welding them to form a top plate;
[0014] (4) The liquid wick with the micro-nano multi-level pore structure is welded to the top plate and the bottom plate, and the working liquid is injected, degassed and packaged to obtain a heat spreader.
[0015] The present invention utilizes PS microspheres and adhesives that can be industrially prepared on a large scale to deposit a sacrificial structure template on a wire mesh / groove micron structure; utilizes an electrodeposition method to deposit required metal nanoparticles in the gaps between the PS sacrificial spheres; removes the PS sacrificial template by soaking in an organic solvent and annealing treatment, and obtains a conformal metal porous structure with nanopore structural characteristics in the wire mesh / groove micron structure; then utilizes a diffusion welding process to weld support columns to a heat spreader top plate; utilizes a welding process to combine the edges of the bottom plate and the top plate into a whole, and connects an operating pipe; after evacuation, injects the working liquid into the heat spreader, and degassing and packaging to prepare a complete heat spreader, thereby effectively improving the heat transfer capacity, heat transfer efficiency and reliability.
[0016] Wherein, the working liquid includes deionized water, acetone or nanofluid.
[0017] As a preferred embodiment of the present invention, the average particle size of the PS microspheres is 0.5 to 100 μm;
[0018] The binder is a polyvinyl alcohol aqueous solution, and the mass concentration of the polyvinyl alcohol aqueous solution is 2-5%;
[0019] The mass ratio of the PS microspheres to the binder is 1:(0.9-1.1).
[0020] PS microspheres with an average particle size of 0.5 to 100 μm are used, which can effectively enter the pores of the copper mesh to form a connected porous metal structure.
[0021] Among them, the present invention uses polyvinyl alcohol as a binder. Polyvinyl alcohol has good bonding properties and is easily soluble in hot water, and the template is easy to remove. However, if polyadipic acid is used as a binder, the polyadipic acid template is difficult to remove after molding, and a large amount of residues remain after high-temperature calcination.
[0022] Among them, the mass ratio of the PS microspheres and the binder has a significant influence on the effect. By controlling the mass of the two within this range, a dense, interconnected porous metal foam structure can be formed. If the mass ratio is less than 1:1, the solution is too dilute and it is not easy to form a dense PS ball template, which will dissolve in the subsequent electrodeposition process; if the mass ratio is greater than 1:1, the solution is viscous and the thickness of the formed template will be uneven, resulting in uneven distribution of the electrodeposited nanostructure and failure to form a complete interconnected porous structure.
[0023] As a preferred embodiment of the present invention, the thickness of the emulsion coating is 1 to 2 mm.
[0024] As a preferred embodiment of the present invention, the current of the electrodeposition is 0.1-1A, the deposition time is 1-4h, and the electrodeposition temperature is 30-50°C.
[0025] Among them, the parameters of the electrodeposition are controlled so as to generate uniform and refined nano-crystals in the gaps between the PS microspheres, and finally a micro-nano multi-level liquid-absorbing core is prepared. If the electrodeposition temperature is too low, the deposition speed is slow; if the temperature is too high, a dendrite structure is easily formed; if the current is too large, the grains are coarse and easy to agglomerate; if the current is too small, a connected mesh structure cannot be formed; if the time is too long, the grains grow densely, resulting in the pores being filled and the loss of active sites.
[0026] As a preferred embodiment of the present invention, the electrodeposition solution is prepared from a saturated sulfate solution and a sulfuric acid solution, and the pH of the electrodeposition solution is 0.8-1.2; the sulfate solution includes at least one of a copper sulfate solution and a nickel sulfate solution.
[0027] As a preferred embodiment of the present invention, the organic solvent includes at least one of tetrahydrofuran and acetone, and the immersion temperature is 30-40°C.
[0028] As a preferred embodiment of the present invention, the annealing temperature is 400-600° C., and the annealing time is 1-3 hours.
[0029] As a preferred embodiment of the present invention, the wire mesh is a 50-200 mesh copper mesh.
[0030] The present invention also provides an application of a heat spreader in a 5G base station, an electronic chip, and an LED.
[0031] The beneficial effects of the present invention are as follows: the liquid-absorbing core with a micron-nano multi-level pore structure of the present invention has a micron structure and a conformal porous metal foam structure with nanopore characteristics, and has the characteristics of large capillary driving force, high permeability and small flow resistance. This type of heat spreader has low production cost, simple method, large heat transfer capacity, high heat transfer efficiency and high reliability, and can be used to make a large-area heat spreader to meet the heat dissipation requirements of electronic equipment with high heat flux density; and the micron-nano multi-level structure of the present invention can be further used for the inner wall of a heat pipe that requires a high capillary driving force and other radiators to meet the needs of rapid heat dissipation, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic structural diagram of the heat spreader of the present invention.
[0033] Figure 2 This is a picture of the bottom plate after drying in Example 1.
[0034] Figure 3 This is a scanning electron microscope image of the bottom plate after drying in Example 1.
[0035] Figure 4 This is a picture of the substrate after electrodeposition for 1 hour in Example 1.
[0036] Figure 5 This is a picture of the bottom plate after being soaked in tetrahydrofuran in Example 1.
[0037] Figure 6 This is a scanning electron microscope image of the bottom plate after being soaked in tetrahydrofuran in Example 1.
[0038] Figure 7 This is a scanning electron microscope image of Example 1 after annealing.
[0039] Figure 8 This is a picture of one end of the support column of Example 1 welded to the base plate using a diffusion welding process.
[0040] Fig. 9 This is a photo of the heat spreader in Example 1, in which the edges of the bottom plate and the top plate are welded together to form an integral whole.
[0041] Fig.10 This is the thermogravimetric curve of the PS ball of Example 1.
[0042] Fig.11 This is a picture of Example 2 after electrodeposition for 4 hours, tetrahydrofuran immersion, and annealing. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0044] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0045] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0046] In the present application, there is no particular limitation on the specific dispersion and stirring treatment methods.
[0047] Unless otherwise specified, the components, raw materials or instruments used in the embodiments and comparative examples of the present invention are all commercially available raw materials or instruments, and the components and raw materials used in each parallel experiment are all of the same kind.
[0048] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0049] The following examples are provided to facilitate understanding of the present invention. These examples are not provided to limit the scope of the claims.
[0050] Example 1
[0051] like Figure 1 As shown, this embodiment provides a heat spreader, including a bottom plate 1, a liquid absorbent core 2 with a micro-nano multi-level pore structure, a support column 3, and a top plate 4, wherein the bottom plate and the top plate form a vacuum cavity, the liquid absorbent core with the micro-nano multi-level pore structure and the support column are located inside the vacuum cavity, the support column connects the bottom plate and the top plate, and the vacuum cavity is filled with working liquid.
[0052] The method for preparing the vapor chamber comprises the following steps:
[0053] (1) A 0.4 mm C5191 copper bottom plate and a 0.4 mm C5191 copper top plate are provided by a stamping method, and a 100 mesh copper wire mesh is placed on the surface of the bottom plate;
[0054] (2) PS microspheres and a polyvinyl alcohol aqueous solution with a mass concentration of 4% were mixed in a mass ratio of 1:1 to obtain an emulsion, which was applied to the surface of the base plate with a coating thickness of 1 mm and dried. The picture after drying is shown in the figure below. Figure 2 As shown; the scanning electron microscope image after drying is as shown Figure 2 As shown, it can be seen that the PS balls are evenly covered on the surface of the copper mesh, presenting a regularly arranged microsphere structure.
[0055] (3) The saturated copper sulfate solution is adjusted to pH 1 with sulfuric acid solution to obtain an electrodeposition solution, and the electrodeposition solution is deposited on the surface of the bottom plate by an electrodeposition method. The electrodeposition current is 0.5 A and the electrodeposition temperature is 40° C.
[0056] like Figure 4 As shown in the photo of the bottom plate after electrodeposition for 1 hour, it can be seen that the PS ball template on the surface has not fallen off, which indicates that the template can still maintain good stability in the strongly acidic electrodeposition solution without falling off or dissolving.
[0057] (4) Soak in tetrahydrofuran for 24 hours. Figure 5 As shown, the photo of the substrate after being soaked in tetrahydrofuran shows that the surface template has been almost completely removed, which indicates that organic solvents can effectively remove the PS sphere template on a macro scale.
[0058] The scanning electron microscope image after immersion in tetrahydrofuran is as follows Figure 6 As shown, it can be seen that a small amount of PS sphere template remains.
[0059] (5) Annealing at 500°C in an argon atmosphere for 2 h; Figure 7 As described above, after annealing, the scanning electron microscope image is as follows Figure 7 As shown, it is found that the template has been completely removed, showing the characteristics of nanostructured pores, and the absorbent core with micro-nano multi-level pore structure is fully washed with water, blown dry and weighed.
[0060] (6) Figure 8 The support column, the liquid-absorbing core with a micro-nano multi-level pore structure, the top plate and the bottom plate are welded, and the surface coating is smooth and uniform.
[0061] (7) Working liquid is injected, degassing is performed, and the edges of the bottom plate and the top plate are welded together to form an integral heat spreader, such as Fig. 9 As mentioned above, the edge of the base plate must be smooth, flat and clean to facilitate welding.
[0062] Fig.10 The thermogravimetric curve of the PS ball template is given. It can be seen that when the temperature reaches 500℃, the weight of the PS ball is almost 0, and the PS ball can be completely removed above 500℃.
[0063] Example 2
[0064] The difference between Example 2 and Example 1 is that the electrodeposition time is 4 hours, and the other parameters are exactly the same as those of Example 1. Fig.11 As shown, conformal porous metal foams with nanostructured pore features were found after prolonged electrodeposition time, and the PS sphere template was also completely removed.
[0065] Example 3
[0066] The difference between Example 3 and Example 1 is that the bottom plate and the top plate are made of stainless steel.
[0067] Example 4
[0068] The difference between Example 4 and Example 1 is that nickel sulfate solution is used to replace copper sulfate (to form a common porous nickel foam).
[0069] Example 5
[0070] The difference between Example 5 and Example 1 is that the emulsion is applied to the surface of the base plate with a coating thickness of 2 mm.
[0071] Example 6
[0072] The difference between Example 6 and Example 1 is that the annealing temperature is 400°C.
[0073] Example 7
[0074] The difference between Example 7 and Example 1 is that the annealing temperature is 600°C.
[0075] Comparative Example 1
[0076] The difference between Comparative Example 1 and Example 1 is that the emulsion is coated on the surface of the base plate with a coating thickness of 0.5 mm. In this comparative example, since the coating thickness is too low, the template dissolves and falls off in the acidic electrodeposition solution, and the suction filter element cannot be prepared.
[0077] Comparative Example 2
[0078] The difference between Comparative Example 2 and Example 1 is that the annealing temperature is 800° C., which is too high, and the nanostructure is destroyed, so the suction filter element cannot be prepared.
[0079] Comparative Example 3
[0080] The difference between Comparative Example 3 and Example 1 is that the annealing temperature is 300°C.
[0081] Comparative Example 4
[0082] The difference between Comparative Example 4 and Example 1 is that the mass ratio of PS microspheres to the polyvinyl alcohol aqueous solution with a mass concentration of 4% is 1:0.5.
[0083] Comparative Example 5
[0084] The difference between Comparative Example 5 and Example 1 is that the mass ratio of PS microspheres to the polyvinyl alcohol aqueous solution with a mass concentration of 4% is 1:2.
[0085] Test Case
[0086] The performance of the vapor chambers obtained in the examples and comparative examples is shown in Table 1.
[0087] Double 85 performance test: Place the sample at 85% humidity and 85℃ and test for 168h according to the method of GB / T 2423.50.
[0088] Table 1
[0089]
[0090]
[0091] It can be seen from Table 1 that the vapor chamber of the present invention has excellent heat transfer efficiency and reliability.
[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A heat sink, characterized in that: It includes a bottom plate, a top plate, a liquid-absorbing core with a micro-nano multi-level pore structure and a support column, wherein the bottom plate and the top plate form a vacuum cavity, the liquid-absorbing core with the micro-nano multi-level pore structure and the support column are located inside the vacuum cavity, the support column connects the bottom plate and the top plate, and the vacuum cavity is filled with working liquid.
2. The vapor chamber according to claim 1, characterized in that: The thickness of the bottom plate and the top plate are both 0.01-0.1 mm, and the materials of the bottom plate and the top plate are both copper alloy, aluminum alloy, stainless steel or titanium alloy.
3. The method for preparing a vapor chamber according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) providing a bottom plate, wherein the surface of the bottom plate has a wire mesh or a groove; (2) mixing the PS microspheres and the binder uniformly to obtain an emulsion, applying the emulsion to the surface of the base plate, drying, depositing an electrodeposition liquid on the surface of the base plate by an electrodeposition method, soaking in an organic solvent, and annealing to obtain a liquid wick having a micro-nano multi-level pore structure; (3) placing the support column and the base plate on the stamping die and welding them to form a top plate; (4) The liquid wick with the micro-nano multi-level pore structure is welded to the top plate and the bottom plate, and the working liquid is injected, degassed and packaged to obtain a heat spreader.
4. The method for preparing a vapor chamber according to claim 3, characterized in that: The average particle size of the PS microspheres is 0.5 to 100 μm; The binder is a polyvinyl alcohol aqueous solution, and the mass concentration of the polyvinyl alcohol aqueous solution is 2-5%; The mass ratio of the PS microspheres to the binder is 1:(0.9-1.1).
5. The method for preparing a vapor chamber according to claim 3, characterized in that: The thickness of the emulsion coating is 1 to 2 mm.
6. The method for preparing a vapor chamber according to claim 3, characterized in that: The current of the electro-deposition is 0.1-1A, and the deposition time is 1-4h.
7. The method for preparing a vapor chamber according to claim 3, characterized in that: The electrodeposition solution is prepared from a saturated sulfate solution and a sulfuric acid solution, and the pH of the electrodeposition solution is 0.8-1.2; the sulfate solution includes at least one of a copper sulfate solution and a nickel sulfate solution.
8. The method for preparing a vapor chamber according to claim 1, characterized in that: The organic solvent includes at least one of tetrahydrofuran and acetone, and the immersion temperature is 30-40°C.
9. The method for preparing a vapor chamber according to claim 1, characterized in that: The annealing temperature is 400-600° C., and the annealing time is 1 h-3 h.
10. Application of the heat spreader described in any one of claims 1 to 2 in 5G base stations, electronic chips, and LEDs.
Citation Information
Patent Citations
Method for manufacturing uniform-heating plate with foam copper as liquid absorption core
CN104764350A
Manufacturing method of soaking plate with ultrathin foam silver as liquid absorbing core
CN104896983A
Inverse opal copper capillary wick structure and manufacturing method thereof
CN116147390A
Copper fiber capillary paste for ultrathin vapor chamber as well as preparation method and application method of copper fiber capillary paste
CN116731687A
Method for preparing vapor chamber upper cover plate, and vapor chamber
WO2022104882A1
Cited By
Vapor chamber, preparation method thereof and electronic equipment
CN121078677A
